(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2024)
Purpose: The viability of companies in today’s turbulent and dynamic market depends on their ability to change and develop together with the market. Primarily under the influence of technological innovations and new customer demands, the logistics sector is under great pressure of change. The focus of this paper is on the functioning of the distribution hub as an important node in the distribution network and the operational processes it implements. The aim of the paper is to investigate different variants of the development of logistics processes in the distribution hub and thus help decision-makers in deciding on the level and performance of potential technological improvement. Methodology: The research was conducted in a real distribution hub using a simulation approach. In particular, discrete event simulation (DES) was used, which allows supporting the dynamics of logistics processes, examining the impact of random variables on processes and determining process performance in different scenarios. Two models were formed in the paper: the As-Is model that imitates the existing processes in the distribution hub, and the To-Be model that assumes a higher technological level of the process. Results: Findings from this paper have two practical implementations. The first one is to use As-Is models as an insight into the current situation in the distribution hub. The second implementation is to use a To-Be model as a decision support system for evaluating different solutions in the execution of logistics processes. Conclusion: The obtained research results provide an opportunity to examine different ways of the functioning of processes in the distribution hub before making changes in the real system, which is especially important for managers of such systems.